ANALISIS TENTANG PRINSIP DEMOKRASI DESA DALAM PENYELENGGARAAN PEMERINTAHAN DI KAMPUNG PINANG SEBATANG KECAMATAN TUALANG KABUPATEN SIAK - Norkolis, Norkolis; Erlinda, Sri; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the phenomenon of the implementation of the principle of village democracy, namely the lack of transparency in RT elections that are not in accordance with the procedures and election requirements mentioned in the Siak Regency Regulation no. 7 of 2010 on the amendment of Local Regulation no. 15 Year 2007 on social institutions. RT selection through deliberation but it is not executed. The formulation of the problem is How the implementation of the principle of village democracy in governance in Village Pinang Sebatang according to the perception of government and society and how the Government of Village Pinang Sebatang in building democratization of the village according to the perception of government and society. This study aims to determine the implementation of the principle of village democracy according to the perception of government and society. As well as the Village Pinang Sebatang Village's efforts to build village democracy according to the government and society. Respondent that is 40 people by using technique of Purposive Sampling. Techniques of collecting data through observation, questionnaires, interviews, and documentation. The research method is quantitative descriptive method. Based on the result of research, the implementation of village democracy principle is in good category (51% - 100%) that is according to government perception 96% and society perception 69%. While efforts to build village democratization are in the category of existing efforts (51% - 100%), that is according to the perception of the village government by 96% and the public perception of 61%.Keywords: Principles of Village Democracy